Retaining talent : an empirical study of multi-routes model of job coupling and withdraw tendency among Chinese MBA candidates / Zheng Weibo - Zheng, Weibo (2010)

(untitled)
Intellectual property and intellectual capital have become critical components of wealth creation. "Knowledge has become the pre-eminent economic resource, more important than raw material, more important, often, than money. Considered as an economic output, information and knowledge are more important than automobiles, oil, steel or any of the products of the industrial era‖ (Stewart, 2002). As the "carrier" of the talent of organizations become more significant than ever. Those employees with higher organizational performance characteristics are often entitled "core" or "talent" for their key networking status in creating organizational intelligent capital values. They can also be in fierce competition with others in the market given the scarcity of vacancies. In the field of talent' retention/ turnover, the empirical study of social relation-oriented between talents' performance characteristics (KDS) and voluntary turnover (withdraw tendency) by modeling take the lead in highlighting talents‘ turnover mechanism. And in recent years the newly-developed "job and community cross centrality" construct model from the retention scope has become a fresh focus and is referred to by the main stream for its advantages with stresses on the contemporary humanity merits canonized in knowledge era, more effective explanation and contributions to the traditional attitudinal turnover model from the platform of job satisfaction and organizational commitment only. This paper, with the background of modern social capital theory, begins from performance-decision issues, focuses on constructing the talents' organizational performance characteristics (KDS) and withdraw tendency model by introducing job coupling constructs and ways of combining literature methodology and empirical study. Significant results with cross-sectioned datum confirmatory analysis have been attained as follows: (1) Talents' performance measuring characteristics are operationally defined as the KDS with integration of seven dimensions based on organizational social capital theory. Its scale is developed with significant inner coherence and constructed to meet the demand of reliability and validity for anonymous questionnaires. (2) Allen‘s model (2001) is introduced with extended hypotheses showing advantages such as introduced job coupling constructs as mediated variables can helpfully disclose the path mechanism from talents' KDS to their job attitudes; KDS highlights the idiosyncrasy of talents' performance, which can usefully disclose relationships among variables in this model; and hypothetically extended moderators' effecting linkage can helpfully clear the relationship between performance visibility and talents' social networking, which previous research has lacked. (3) From the confirmatory study by LISREL on this paper's model, significant results and some new findings have been attained, both mediated path and moderated factors: job coupling constructs show dominant constraint over the path effects that seem to be the focus for talent retention; job payment is an essential retention factor at present for talents; off-the-job payment may become a compensation mechanism for talents who stay in some lower-pay organizations; family-responsibility of talents' are dual nature, both job family conflict and movement restraint; and talents' performance visibility may come true mainly through their social networking. (4) The difference analysis by SPSS on variables' effects from three groups, based on their nationality, job position or types and different scale of KDS, has given some cues. Talents as technicians or administrators are more homogeneous (lower substitutable and higher tendency to leave), and may be the main groups talents belong to; talents from the mainland of China may be of stronger turnover intent but are under more constraint from their job coupling; talents' withdraw tendencies have double- sided influence from their job coupling; the institutionalized retention and off-the-job professional growth motivation for talents may be the key issues for attaining higher job satisfaction, organizational commitment and effective retention results. (5) According to the theory of employees' decisions to participate, decision to perform and modern retention theories (March and Simon, 1958; Allen, 2001; Mitchell, 2004), an effective retention view-- scoped model is developed based on which, both from the job but also from community coupling- oriented comprehensive retention suggestions are made. Finally, research works are summarized and some extending perspectives are put forward from some limitations of this paper.